The biodistribution and pharmacokinetics of the oxime acetylcholinesterase reactivator RS194B in guinea pigs. (1st November 2017) - Malfatti, Michael A.; Enright, Heather A.; Be, Nicholas A.; Kuhn, Edward A.; Hok, Saphon; McNerney, M. Windy; Lao, Victoria; Nguyen, Tuan H.; Lightstone, Felice C.; Carpenter, Timothy S.; Bennion, Brian J.; Valdez, Carlos A.
Abstract: Organophosphorus-based (OP) nerve agents represent some of the most toxic substances known to mankind. The current standard of care for exposure has changed very little in the past decades, and relies on a combination of atropine to block receptor activity and oxime-type acetylcholinesterase (AChE) reactivators to reverse the OP binding to AChE. Although these oximes can block the effects of nerve agents, their overall efficacy is reduced by their limited capacity to cross the blood-brain barrier (BBB). RS194B, a new oxime developed by Radic et al. ( J. Biol. Chem., 2012 ) has shown promise for enhanced ability to cross the BBB. To fully assess the potential of this compound as an effective treatment for nerve agent poisoning, a comprehensive evaluation of its pharmacokinetic (PK) and biodistribution profiles was performed using both intravenous and intramuscular exposure routes. The ultra-sensitive technique of accelerator mass spectrometry was used to quantify the compound's PK profile, tissue distribution, and brain/plasma ratio at four dose concentrations in guinea pigs. PK analysis revealed a rapid distribution of the oxime with a plasma t1/2 of ∼1 h. Kidney and liver had the highest concentrations per gram of tissue followed by lung, spleen, heart and brain for all dose concentrations tested. The Cmax in the brain ranged between 0.03 and 0.18% of the administered dose, and the brain-to-plasma ratio ranged from 0.04 at the 10 mg/kg dose to 0.18 at the 200 mg/kg dose demonstrating dose dependent differences in brain and plasma concentrations. In vitro studies show that both passive diffusion and active transport contribute little to RS194B traversal of the BBB. These results indicate that biodistribution is widespread, but very low quantities accumulate in the guinea pig brain, indicating this compound may not be suitable as a centrally active reactivator. Highlights: Plasma PK of RS194B is linear with dose and follows first order kinetics. RS194B is rapidly distributed from the plasma to peripheral tissues. RS194B does not effectively cross the blood-brain-barrier. RS194B does not significantly accumulate in the brain.